Development theory and the three Worlds - Hettne, Bjorn (New York, 1990)
The result of a theory that arose with a SAREC (Swedish Agency for Research Cooperation with Developing Countries) workshop on development theory in 1977, this book sees development theory as a set of theories relevant for understanding development problems in different geographical and historical contexts. It is a history of development thinking which provides a survey of social science theories to aid understanding of development problems in different countries with varying histories. It examines not only the Third World, but also Western industrial countries and the socialist world. The series is designed for use in courses in colleges and universities in the developing world. It should also be useful for sixth-form and undergraduate students, teachers and general readers in the developed world, international agencies, development organizations and charities.
Keywords: Economic development